TRANSFORMASI HARIAN PAGI RADAR BOGOR DALAM MEMPERTAHANKAN EKSISTENSI MEDIA - Nisfa Siti Elfianti Hidayah, (2020)
The print media is currently in the midst of the onslaught of the use of the internet, namely online media as a source for finding information needs. Based on this in this study, there are two research questions to be analyzed, namely how the Radar Bogor strategy in transforming to maintain its existence. As well as the steps taken to carry out the transformation. The purpose of this study is to analyze how the strategies and steps taken by Radar Bogor in transforming to maintain its existence or presence in the world of the press. The method used in this research is qualitative with a case study approach. Data collection techniques are done by interview and observation. The data analysis technique used is the interactive data analysis model from Miles and Huberman consisting of data reduction, data presentation, and drawing conclusions or verification. Based on the data analysis conducted in this study, it was concluded that the concept of transformation carried out by Radar Bogor had the same concept as that of Roger Fidler's mediamorphosis theory. The concept consists of coevolution, convergence and complexity (chaos). The transformation carried out is a strategy carried out by Radar Bogor as an effort to maintain its presence in the world of the press, as evidenced by the 21 years that Radar Bogor has remained present maintaining its newspaper production in large numbers and transforming towards digital to keep abreast of technology.